Magnetic Behavior of a Laser Deposited Fe–Ni–Mo Alloy. Issue 6 (12th January 2023) - Firdosy, Samad; Ury, Nicholas; Dang, Katherine; Narvaez, Pablo; Witt, Ronald; Berman, Joshua; Cooperrider, Joelle; Dillon, Robert Peter; Ravi, Vilupanur A.
Abstract : Magnetic shielding in spacecraft is a mission‐critical issue that must be addressed in a timely and effective manner. The high permeability of Fe–Ni–Mo alloys, makes them excellent candidates for magnetic shielding. This article explores a new and innovative approach, enabled by additive manufacturing (AM), to design, build, and test geometrically complex magnetic shields. A Fe–79.7Ni–4.1Mo alloy is additively manufactured using blown powder laser‐directed energy deposition (DED). AM build conditions are explored in the production of magnetic test rings and magnetic shield prototypes. Magnetic hysteresis test data are obtained, allowing for the determination of magnetic permeability, saturation, and coercivity. Detailed microstructural characterization is carried out. Three different prototype shield designs are printed and magnetic shield attenuation data is obtained. The magnetic field attenuation (shield effectiveness) obtained for the AM components is comparable to wrought equivalents. The values reported here for the magnetic permeability are the highest, and that for the magnetic coercivity the lowest, for any blown powder DED‐printed material currently known. The magnetic behavior is discussed with regard to grain size and orientation, as well as grain boundary effects, with all of these attributes contributing to the ultimate performance. Abstract : Magnetic shielding in spacecraft is a mission‐critical issue that must be addressed in a timely and effective manner. The high permeability of Fe–Ni–Mo alloys, make them excellent candidates for magnetic shielding. This article explores a new and innovative approach, enabled by additive manufacturing (AM), to design, build and test geometrically complex magnetic shields.